PENGEMBANGAN MODEL PEMBELAJARAN KESEIMBANGAN DALAM PENJASORKES MELALUI PERMAINAN POST BALANCE PADA SISWA KELAS III SEKOLAH DASAR (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The objective of this study is to produce the development of balance teaching model through post balancebalance that suits the characteristic. The research methodology of this study is research-based development thatrefers to Borg & Gall’s development model with some modifications: (1) need analysis, (2) development of firstproduct, (3) evaluation of experts, (4) revision of the first product (10 students), (5) field investigation (39students), (6) revision of the last product, (7) the last result of balance teaching model. The technique ofanalyzing the data is descriptive persentages for the aspect of psycomotoric, kognitive and affective of thestudents after applying the product.From the data evaluation done by experts (one phisical education experticeand two teaching experts), gained the answers for the category of\ very poor 0%, poor 0%, fairly good, 0%,good 69,77%, and very good 30,23%. From the questionnaire data, it is gained the answers for category of verypoor0%, poor 0%, fairly good 16,67%, good 3,33%, and very good 80%.It is concluded that post balance gameis efective and suitable with students’ characteristics so that this game can be used in physical teaching.